Nitrogen-doped soft carbon frameworks built of well-interconnected nanocapsules enabling a superior potassium-ion batteries anode - Liu, Chang; Xiao, Nan; Li, Hongjiang; Dong, Qiang; Wang, Yuwei; Li, Hongqiang; Wang, Shuaifeng; Zhang, Xiaoyu; Qiu, Jieshan (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
A high-performance potassium-ion battery anode is achieved by using nitrogen-doped soft carbon frameworks with high electronic and ionic conductivity. [Display omitted] •N-doped soft carbon frameworks have been fabricated by MgO template method.•The N-doped soft carbon shows rapid electron transfer and K+ diffusion.•The N-doped soft carbon anode presents a superior rate performance and ultra-stable cycle life.•The ordered N-doped carbon clusters with enlarged interlayer distance may responsible for the superior rate performance. Potassium-ion batteries (PIBs) have been regarded as one of the most promising alternatives to traditional lithium-ion batteries because of the low cost and abundant reserves of potassium resources. However, it is challenging to achieve suitable anode materials with long cycle life and high rate performance. Herein, nitrogen-doped soft carbon frameworks built of well-interconnected nanocapsules have been fabricated as facile and effective anodes for PIBs. The anode delivers a high specific capacity of 293 mAh g−1 at 0.05 A g−1 and 151 mAh g−1 at 5 A g−1 with a rate capability of 51.5%. It retains 85.5% capacity retention at 1 A g−1 after 500 cycles. The excellent rate performance can be mainly ascribed to the high ionic and electronic conductivity, resulted from the ordered nitrogen-doped carbon clusters with enlarged interlayer distance. The interconnected hierarchically porous structure further promotes K+ diffusion kinetics.